Future workscapes : strategic insights and innovations in human resources and organizational development - Paliszkiewicz, Joanna; Varoğlu, Demet; Kulykovets, Olena (International perspectives on equality, diversity and inclusion, 2025)
In an era where technological advancements, shifting societal norms, and global challenges are fundamentally reshaping the landscape of work, Future Workscapes emerges as a pivotal publication. The first of two parts, this volume delves into critical aspects of the modern workplace by analyzing the evolution of work environment and human resource strategies and organizational development. Chapters focus on techno-empowerment, transportation services, co-working spaces, digital transformation and logistics, consumer behavior, networking, and more. Through qualitative research and case studies, authors provide insights into creating technologically advanced, human-centric and inclusive organizations. Both Part A and B of Future Workscapes offers an in-depth exploration of the evolving work environment and human resource strategies, addressing the urgent need for organizations to adapt to rapid changes, fostering environments that are not only technologically advanced but also human-centric, sustainable, and inclusive.